2014
DOI: 10.2337/dc13-1212
|View full text |Cite
|
Sign up to set email alerts
|

Health-Related Quality of Life Predicts Major Amputation and Death, but Not Healing, in People With Diabetes Presenting With Foot Ulcers: The Eurodiale Study

Abstract: Low health-related quality of life (HRQoL) has been consistently reported to be associated with poor prognosis for a variety of health outcomes in various settings. We aimed to evaluate whether HRQoL in patients presenting with new diabetic foot ulcers (DFUs) has prognostic significance for ulcer healing, major amputation, and death. RESEARCH DESIGN AND METHODSWe followed 1,088 patients with new DFUs presenting for treatment at one of the 14 centers in 10 European countries participating in the Eurodiale (Euro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
58
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(65 citation statements)
references
References 37 publications
4
58
0
3
Order By: Relevance
“…42 However, it is usually the combined effect of macrovascular and microvascular complications, comorbid conditions, and background demographic, clinical and treatment satisfaction variables which degrade HRQoL and not diabetes per se. 43 The results of the known-groups comparisons performed here conform to the literature 1,[12][13][14][15]17,[27][28][38][39][40][41] in terms of the score differences and the direction of these differences.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…42 However, it is usually the combined effect of macrovascular and microvascular complications, comorbid conditions, and background demographic, clinical and treatment satisfaction variables which degrade HRQoL and not diabetes per se. 43 The results of the known-groups comparisons performed here conform to the literature 1,[12][13][14][15]17,[27][28][38][39][40][41] in terms of the score differences and the direction of these differences.…”
Section: Discussionsupporting
confidence: 77%
“…The overall results for the psychometric properties [38][39][40][41] but in the end their absence can be taken as evidence that the instrument is sensitive at its lower end. All SF-36 mean scale scores (not shown) were lower than the respective general population scores reported in the instrument validation study.…”
Section: Discussionmentioning
confidence: 93%
“…The interdisciplinary treatment plan should consider not only clinical factors but also patients' experiences and perceptions . Furthermore, when medical professionals take a patient‐oriented approach, assessing patients' experiences and understanding and how they have been treated for diabetes and its complications, they could give prescriptions and education tailored to individual patients, which would greatly help patients manage their diabetic feet preventatively …”
Section: Introductionmentioning
confidence: 99%
“…Conversely, one Scottish study considered healthcare accessibility as well as socioeconomic disadvantage in the population and demonstrated evidence of increased foot ulceration in the more disadvantaged areas within Scotland [21]. The Eurodiale study has reported that low health-related quality of life is predictive of major amputation and mortality [22].…”
Section: Introductionmentioning
confidence: 99%